Status of VEPP-4M collider: current activity and plans - Blinov, V.; Bogomyagkov, A.; Karnaev, S.; Kiselev, V.; Kremyanskaya, E.; Kvardakov, V.; Levichev, E.; Mishnev, S.; Meshkov, O.; Muchnoy, N.; Naumenkov, A.; Neyfeld, V.; et al. (Вопросы атомной науки и техники, 2006)
Presented are the results of a VEPP-4M collider operation at Budker Institute of Nuclear Physics during
2004-2005 as well as the plans for the nearest future. Представлены результаты, полученные на накопителе ВЭПП-4М Института Ядерной физики им. Будкера, за период 2004-2005 г., а также планы на ближайшее будущее. Представлено результати, отримані на накопичувачі ВЕПП-4М Інституту Ядерної фізики ім. Будкера, за період 2004-2005 р., а також плани на найближче майбутнє